A nonsense mutation in the tyrosinase gene causes albinism in water buffalo - Florisbal Dame, Maria Cecilia; Xavier, Gildenor Medeiros; Oliveira-Filho, Jose Paes [UNESP]; Borges, Alexandre Secorun [UNESP]; Oliveira, Henrique Nunes de [UNESP]; Riet-Correa, Franklin; Schild, Ana Lucia (Biomed Central Ltd., 2012)
Background: Oculocutaneous albinism (OCA) is an autosomal recessive hereditary pigmentation disorder affecting humans and several other animal species. Oculocutaneous albinism was studied in a herd of Murrah buffalo to determine the clinical presentation and genetic basis of albinism in this species.Results: Clinical examinations and pedigree analysis were performed in an affected herd, and wild-type and OCA tyrosinase mRNA sequences were obtained. The main clinical findings were photophobia and a lack of pigmentation of the hair, skin, horns, hooves, mucosa, and iris. The results of segregation analysis suggest that this disease is acquired through recessive inheritance. In the OCA buffalo, a single-base substitution was detected at nucleotide 1,431 (G to A), which leads to the conversion of tryptophan into a stop codon at residue 477.Conclusion: This premature stop codon produces an inactive protein, which is responsible for the OCA buffalo phenotype. These findings will be useful for future studies of albinism in buffalo and as a possible model to study diseases caused by a premature stop codon.
Keywords: Albinism; Buffalo; Nonsense mutation; Stop codon; Tyrosinase